Role of Vanadium Carbide in Hydrogen Embrittlement of Press-Hardened Steels: Strategy From 1500 to 2000 MPa - Lin, Yi-Ting; Yi, Hong Liang; Chang, Zhi Yuan; Lin, Hsin-Chih; Yen, Hung-Wei (Frontiers in Materials, 2021)
This work investigated hydrogen trapping and hydrogen embrittlement (HE) in two press-hardened steels, 22MnB5 for 1,500 MPa grade and 34MnB5V for 2000 MPa grade, respectively. Superior to the 22MnB5 steel, the newly developed 34MnB5V steel has an ultimate tensile strength of over 2000 MPa without sacrificing ductility due to the formation of vanadium carbides (VCs). Simulated press hardening was applied to two steels, and hydrogen was induced by cathodic charging. Susceptibility to HE was validated by slow strain-rate tensile test. When hydrogen content was high, the 34MnB5V steel fractured in elastic regime. However, when hydrogen content was 0.8–1.0 ppmw, the 34MnB5V steel bore much higher stress than the 22MnB5 steel before fracture. The behavior of hydrogen trapping was investigated by thermal desorption analyses. Although the two steels trapped similar amounts of hydrogen after cathodic charging, their trapping mechanisms and effective trapping sites were different. In summary, a finer prior austenite grain size due to the pinning effect of VCs can also improve the toughness of 34MnB5V steel. Moreover, trapping hydrogen by grain boundary suppresses the occurrence of hydrogen-enhanced local plasticity. Microstructural refinement enhanced by VCs improves the resistance to HE in 34MnB5V steel. Importantly, the correlation between hydrogen trapping by VCs and improvement of HE is not significant. Hence, this work presents the challenge in designing irreversible trapping sites in future press-hardened steels.